2008
DOI: 10.1080/19322880802266805
|View full text |Cite
|
Sign up to set email alerts
|

Ethnoracial Minority Background, Psychological Trauma, PTSD, and DESNOS Among Urban Low-Income Women with Severe Mental Illness

Abstract: Psychological trauma and posttraumatic stress disorder (PTSD) are prevalent among adults with severe mental illness. A sample of 38 women in intensive community mental health services was assessed with psychometrically validated structured interview measures. Exposure to multiple types of psychological traumas was reported by 95% of respondents; almost half (44%) met criteria for current PTSD, and an equal number met criteria for Disorders of Extreme Stress Not Otherwise Specified (DESNOS). Another 40% did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
(46 reference statements)
2
11
1
Order By: Relevance
“…As has been found in other studies of urban, treatment-seeking individuals, our study found a significant relationship between Black race and increased religiosity (Ford, 2008). Religious teachings promote a sense of hope (Lizardi et al, 2008), which may decrease depressive symptoms among Blacks.…”
Section: Discussionsupporting
confidence: 91%
“…As has been found in other studies of urban, treatment-seeking individuals, our study found a significant relationship between Black race and increased religiosity (Ford, 2008). Religious teachings promote a sense of hope (Lizardi et al, 2008), which may decrease depressive symptoms among Blacks.…”
Section: Discussionsupporting
confidence: 91%
“…The DESNOS concept and diagnosis has not been investigated previously in Scandinavia. The few published studies of war victims and minority populations have found substantial differences in the prevalence of DESNOS (Morina & Ford, 2008; Ford, 2008), as well as little support for the cross‐cultural DESNOS construct (de Jong, Komproe, Spinazzola, van der Kolk & Van Ommeren, 2005). Even if the DESNOS diagnosis is not included as a formal and separate diagnosis in the DSM‐IV, its practical value in treating multiple trauma patients is still important.…”
Section: The Rationale and The Purpose Of The Studymentioning
confidence: 99%
“…Similarly, in Ford's study (2008) a high number of urban low income women with severe mental disorders met the criteria for PTSD diagnosis (44%) and subthreshold PTSD (44%) [25] . Women in a disadvantaged neighborhood with increased exposures to traumatic events may fall into this Bsubthreshold^category of PTSD and experience increased psychological distress despite not having the Bfull-blown^PTSD diagnosis.…”
Section: Discussionmentioning
confidence: 97%